Enrico Fermi's IEEE Milestone in Florence. For his Major Contribution to Semiconductor Statistics, 1924-1926 - manes, gianfranco; Pelosi, Giuseppe (I libri de «Il Colle di Galileo», 2015)
Enrico Fermi, Nobel Laureate in Physics in 1938, taught at the University of Florence just for two academic years (1924-25 and 1925-26). His research activity in these two years saw the publication of the statistics bearing his name (the two original 1926 papers by E. Fermi are reproduced in full in this book), which is at the basis of semiconductors, and hence of modern electronics. This volume is printed for the placement, at the School of Engineering in Florence, of an IEEE Milestone, within the 'IEEE Global History Network program', commemorating the event. The IEEE (Institute of Electrical and Electronic Engineers) is the largest professional association in the world devoted to advancing technological innovation in electrical, electronic engineering, and related fields.